2012
DOI: 10.2967/jnumed.111.102434
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Zinc-Telluride Myocardial Perfusion Imaging in Obese Patients

Abstract: We have evaluated the impact of increased body mass on the quality of myocardial perfusion imaging using a latest-generation g-camera with cadmium-zinc-telluride semiconductor detectors in patients with high ($40 kg/m 2 ) or very high ($45 kg/m 2 ) body mass index (BMI). Methods: We enrolled 81 patients, including 18 with no obesity (BMI , 30 kg/m 2 ), 17 in World Health Organization obese class I (BMI, 30-34.9 kg/m 2 ), 15 in class II (BMI, 35-39.9 kg/m 2 ), and 31 in class III (BMI $ 40 kg/m 2 ), including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…Furthermore, due to limited FOV of the new systems, it is possible to truncate heart data on some views, leading to truncation artifacts, especially in larger patients. 86 In addition, a unique collimator/detector geometry can lead to 3D sensitivity variations. 85 Therefore, attenuation of photons and other sources of imaging artifacts need to be recognized correctly on these systems by the users.…”
Section: Solid-state Camerasmentioning
confidence: 99%
“…Furthermore, due to limited FOV of the new systems, it is possible to truncate heart data on some views, leading to truncation artifacts, especially in larger patients. 86 In addition, a unique collimator/detector geometry can lead to 3D sensitivity variations. 85 Therefore, attenuation of photons and other sources of imaging artifacts need to be recognized correctly on these systems by the users.…”
Section: Solid-state Camerasmentioning
confidence: 99%
“…Based on integrated collimator geometry modeling, 40 and 50 iterations of the al- It was reported that for patients with morbid obesity, MPI on CZT cameras might often yield insufficient image quality. 43 Because the body mass is too large for the size of the gantry, the patient's heart cannot be positioned close enough to the detectors. As a result, for the patients with body mass index ≥40 kg/m 2 it is difficult to obtain diagnostic imaging quality on a CZT camera.…”
Section: Czt Gamma Camera Systemmentioning
confidence: 99%
“…Reducing the administered activity may also be important to prolong the use of MPS in the predicted worldwide deficiency of 99m Tc. Examining obese patients with the GE Discovery 530 CZT camera has been reported to be challenging 21,27 due to the limited quality field of view (QFOV) associated with this camera. For patients with a large body habitus, it may be difficult to obtain an b Figure 2.…”
Section: Discussionmentioning
confidence: 99%